Adaptive Osmotic Filtration Mechanisms in Sap-Feeding Insects - mohammed, Nagham Abdulghani; Qader, Fadel Abbas (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Sap-feeding insects consume diets rich in water but poor in essential nutrients, creating major physiological challenges. Specific Background: Many Hemipteran insects possess a specialized digestive modification known as the filter chamber that facilitates sap processing. Knowledge Gap: Although its anatomical presence is well documented, an integrated understanding of its functional mechanisms, molecular basis, and evolutionary diversification remains limited. Aims: This review synthesizes current anatomical, physiological, and molecular findings on the insect filter chamber, with emphasis on digestion, absorption, and evolutionary specialization. Results: Evidence shows that the filter chamber enables rapid osmotic transfer of excess water and sugars from the foregut–midgut directly to the hindgut, supported by aquaporins and sugar transporters, thereby optimizing nutrient retention and metabolic efficiency. Structural complexity varies across taxa, reflecting host-plant adaptation. Novelty: The article integrates classical morphology with recent molecular insights to present the filter chamber as a dynamic regulatory system rather than a passive structure. Implications: Understanding filter chamber function offers prospects for targeted pest management strategies through disruption of specific transport pathways while reducing reliance on broad-spectrum insecticides.Highlights: The filter chamber regulates water and sugar balance during sap feeding. Structural variation reflects evolutionary adaptation to host plants. Transport proteins present potential targets for selective pest control. Keywords:Filter Chamber; Sap-Feeding Insects; Osmotic Regulation; Aquaporins; Digestive Adaptation